THE IMPLEMENTATION OF SQ3R TECHNIQUE IN TEACHING READING COMPREHENSION - Kusumayanthi, Susie; Maulidi, Sely Mariam (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2019)
This study aims to describe the implementation of SQ3R in teaching reading comprehension and to identify students' responses to the implementation of SQ3R. This study uses a qualitative case study conducted at one of the state vocational school in Purwakarta. It involves 4 students. Data were collected through observation and interviews. The data from 2 instruments were analyzed qualitatively. The results of this study indicate that the implementation of SQ3R helps students to understand English words. According to Apandi (2011), SQ3R helps the students to understand English words. The students also responded positively to the implementation of SQ3R. Therefore, SQ3R is recommended to be implemented in teaching reading comprehension.